2014
DOI: 10.2463/mrms.2013-0104
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative T Staging of Urinary Bladder Cancer: Efficacy of Stalk Detection and Diagnostic Performance of Diffusion-weighted Imaging at 3T

Abstract: Purpose: We evaluated the ability of diffusion-weighted imaging (DWI) at 3 tesla for diagnosing T stage and detecting stalks in bladder cancer.Methods: In total, 39 consecutive patients with bladder tumors underwent magnetic resonance (MR) imaging that included T 2 -weighted imaging (T 2 WI) and DWI using a 3T MR scanner. Two radiologists interpreted T 2 WI plus DWI and T 2 WI for diagnosis of T stage and for detection of stalks. We used McNemar's test to examine differences in diagnostic performance and Fishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 17 publications
0
14
0
2
Order By: Relevance
“…Recently, functional imaging has been introduced into the diagnosis of bladder cancer, including DWI MR imaging. Several studies (6,10,11,(17)(18)(19)21) have had a wide range of partially conflicting results for DWI MR imaging in differentiating T1 or lower tumors from T2 or higher tumors. This motivated researchers to perform a recently published meta-analysis (33), which included eight studies published before September 2014 in English or Chinese.…”
Section: Evidence-based Practice: Diagnostic Value Of Mr Imaging In Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, functional imaging has been introduced into the diagnosis of bladder cancer, including DWI MR imaging. Several studies (6,10,11,(17)(18)(19)21) have had a wide range of partially conflicting results for DWI MR imaging in differentiating T1 or lower tumors from T2 or higher tumors. This motivated researchers to perform a recently published meta-analysis (33), which included eight studies published before September 2014 in English or Chinese.…”
Section: Evidence-based Practice: Diagnostic Value Of Mr Imaging In Dmentioning
confidence: 99%
“…It can also help improve the determination of tumor extent. Authors of many studies have investigated the accuracy of MR imaging in local staging (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). These studies differ in their use of magnetic field strengths, combinations of anatomic and functional MR imaging techniques, and number of patients.…”
mentioning
confidence: 99%
“…Finally, DWI was performed in only 29 patients in our study. Numerous studies have demonstrated the value of DWI for the improved characterization of detected renal neoplasms [ 15 , 16 , 57 , 70 74 ]. One such study [ 15 ] showed that the addition of ADC information to CE-MRI findings led to the reclassification of 3 of 6 oncocytomas and 2 of 2 multilocular cystic nephromas that had originally been misdiagnosed as malignant on CE-MRI alone, thereby increasing specificity from 89 to 96 %.…”
Section: Discussionmentioning
confidence: 99%
“…Staging of bladder cancer by DWI alone is in general unsatisfactory [46] , although a study revealed high accuracy of staging bladder cancer with the combination of DWI and T2WI [8] . Staging a tumor with a stalk showing imaging of “inchworm sign” not only is seen in stage Ta or stage T1 tumors but also can be seen in stage T2 tumors [46,57,58] . It is occasionally unable to determinate if the tumor margin is smooth on DWI, which makes the correct categorization of the tumor as stage T2 or stage T3 difficult [8] .…”
Section: Pitfalls and Limitations In Staging Of Bladder Cancermentioning
confidence: 99%